2010
DOI: 10.1152/ajpgi.00367.2009
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal lymph fistula model—a novel approach to study ghrelin secretion

Abstract: The orexigenic hormone ghrelin is secreted from the stomach and has been implicated in the regulation of energy and glucose homeostasis. We hypothesized that ghrelin, like other gastrointestinal (GI) hormones, is present in intestinal lymph, and sampling this compartment would provide advantages for studying ghrelin secretion in rodents. Blood and lymph were sampled from catheters in the jugular vein and mesenteric lymph duct before and after intraduodenal (ID) administration of isocaloric Ensure, dextrin, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Do other gastrointestinal hormones, such as gastrin, secretin, and xenin, have elevated concentrations in lymph versus plasma? It has been recently shown that the lymphatic concentration of ghrelin is also higher than in plasma [88]. Regarding the mechanisms of nutrient-induced incretin secretion, what is the role of nutrient absorption in regulating incretin release?…”
Section: Discussionmentioning
confidence: 99%
“…Do other gastrointestinal hormones, such as gastrin, secretin, and xenin, have elevated concentrations in lymph versus plasma? It has been recently shown that the lymphatic concentration of ghrelin is also higher than in plasma [88]. Regarding the mechanisms of nutrient-induced incretin secretion, what is the role of nutrient absorption in regulating incretin release?…”
Section: Discussionmentioning
confidence: 99%
“…The consortium has published standard operating procedures for measuring food intake (Ellacott et al 2010) and for performing glucose clamps (Ayala et al 2010). Individual MMPCs have published papers describing methods (Ayala et al 2006; Jandacek et al 2004; Kaiyala and Schwartz 2011; Kaiyala et al 2010; Rottman et al 2007; Shearer et al 2008; Tong et al 2010; Yin et al 2011), standards (Ayala et al 2006; McGuinness et al 2009; Rottman et al 2003), and strain comparisons (Berglund et al 2008; Burgess et al 2005; Qi et al 2005). The Vanderbilt MMPC maintains a comprehensive online laboratory manual for in vivo testing (http://www.mc.vanderbilt.edu/mmpc) and has a video of the surgery and glucose clamp that can be viewed online (Ayala et al 2011).…”
Section: Center Activitiesmentioning
confidence: 99%